An Exploration of Coaching as Leadership support for Primary School Principals in Ireland - Breslin, Bláthnaid (Trinity College (Dublin, Ireland). School of Education, 2022)
Empirical data has indicated that the role of the primary school principal has become increasingly challenging due to an increasing workload (Filipov, 2021; Hauseman, Pollock, & Fei, 2017; Hislop, 2022). In 2015 the Department of Education and Skills provided funding for the establishment of the Centre for School Leadership, Ireland (CSL), who then established a professional coaching programme for school principals (CSL, 2015a). This thesis sets out to examine the experiences of Primary Principals of the Centre for School Leadership coaching provision. The aim of the study is to gain an insight into the impact, if any, that coaching as support for school leadership had on participant practice. Research suggests that coaching has an important role to play in the development of leadership skills (Goff, Edward Guthrie, Goldring, & Bickman, 2014; J. Gray, 2018). The coaching programme has been in place since 2016, there is currently a dearth of research into this area in relation to educational leadership in Ireland. Dr. Paul Butler has recently published a PhD thesis on the subject (2020)The data was collected by providing nine primary school principals who had participated in the CSL coaching programme with questionnaires. The Covid-19 pandemic necessitated the move from planned face to face, semi structured interviews to questionnaires. Consultation with willing participants indicated a reluctance to engage in online interviews due to teaching and managing moving into that sphere. They expressed the desire to provide the researcher with feedback through online questionnaires that could be addressed at the participants’ leisure. As the researcher is a serving primary principal, this was fully understood, and the questionnaire was distributed through Google forms. Key findings have been presented and analysed based on a thematic approach. The data revealed that executive coaching provided a number of key benefits for participants in the areas of their reflective practice, affirmation of their leadership, improved goal setting, increased levels of confidence and management of their workload. Respondents reported increased decision-making ability, deeper understanding of their own and their colleagues’ strengths and weaknesses, improved delegation and a better work-life balance. However, participants also reported some negative aspects of coaching around the relationship with the coach, expectations and discomfort with the challenging aspect of coaching which is in keeping with empirical evidence on the subject (K. Korotov, 2012; Korotov, 2015) The study concludes that the CSL coaching programme can provide significant supports for primary school principals but that there are areas for improvement of the service which could serve leadership and management in schools.
Keywords: Leadership; Education